Plum Island - DeMille, Nelson (New York : Warner Books, 1997)
Tom and Judy Gordon were bright, young, attractive scientists whom everyone seemed to like. So who would murder them-and why? Could their deaths have something to do with Plum Island, supposedly an animal research facility but possibly a top-secret site for biological warfare experiments? Could it involve a pirate's treasure buried in the vicinity more than 300 years ago?
A novel
Map on lining papers
Keywords: New York (N.Y.). -- Police Dept. -- Fiction; Treasure troves -- New York (State) -- Long Island -- Fiction; Plum Island (N.Y.) -- Fiction; Mystery fiction